Development of Student Work Sheets Based on Contextual Learning to Facilitate Mathematic Concept Understanding Skill of Junior High School Student 7th Grade - Citra Murti Anggraini; Kristina Warniasih; Padrul Jana (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
The research purpose was to produce learning material as the quality of Student Work Sheets based on contextual learning to facilitate Mathematics concept understanding skill of Junior High School student 7th Grade at triangle material and to describe the quality of Student Work Sheets that has a valid, simple and effective qualification. Student Work Sheets development based on Ministry of Education development model that adapted from Borg and Gall procedure development through some steps: (1) doing product development analysis, (2) developing beginning product, (3) expert’s validation and revision, (4) small-scale field test and product revision, and (5) significant scale field test and last  product. Student Work Sheets quality described based on the marking result of material expert, media expert, and mathematics teacher for the validation aspect, student respond questionnaire and observation sheets of learning application for simplicity aspect, also a post-test question for affectivity aspect. The research result showed that the quality of Student Work Sheets product in validation aspect fulfill good and very good criteria based on the mark from a material expert, media expert, and assessor with the average score for each aspect was 4,19; 4,31; and 4,23. Simplicity aspect fulfills good and very good criteria based on the result of student respond questionnaire and observation sheets of learning application with the average score for each aspect was 3,55 and 93,68%. However, for affectivity aspect fulfill good criteria based on student post-test with the average score was 79,17 from the maximal score was 100 and completeness percentage was 69%.